Flame retardant rubber material, preparation method thereof and sealing strip

By adding ammonium phosphate to graft graphene oxide and imidazole modified MXene to ethylene propylene ternary rubber, an expanded flame retardant system is formed, which solves the problems of poor flammability and flame retardant performance of rubber materials, and achieves efficient flame retardant and mechanical properties improvement.

CN116376179BActive Publication Date: 2025-04-08SAIYANG SEALING ELEMENT ZHEJIANG
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202310446491.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2023-02-20
Filing Date
2023-04-24
Publication Date
2025-04-08
Estimated Expiration
2043-04-24

AI Technical Summary

Technical Problem

Due to its flammability and poor flame retardant performance, EPDM rubber has problems such as high heat release, rapid flame spread and smoke and toxic gas release during fire.

Method used

MXene was modified by adding ammonium phosphate to graft graphene oxide and imidazole into ethylene propylene ternary rubber, and through mechanical blending and grafting reaction, an expanded flame retardant system is formed to improve the flame retardant performance of the material.

Benefits of technology

It realizes efficient flame retardant of the material, reduces the heat release rate and total heat release amount, improves the carbon residue rate, and improves the mechanical properties and dispersion of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116376179B_ABST
    Figure CN116376179B_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a flame retardant rubber material and a preparation method and a sealing strip thereof, wherein EPDM rubber, ammonium phosphate grafted graphene oxide, filler, vulcanizing agent, vulcanization accelerator, lubricant and the like are used as raw materials, a mixed rubber is prepared after blending, and the mixed rubber is further prepared into a sealing strip. The technical solution of the invention mainly solves the defect that the flame retardant effect of EPDM rubber in the prior art is poor.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of rubber modification, in particular to the technical field of EPDM rubber flame retardancy. Background Art

[0002] Ethylene propylene diene monomer (EPDM), like most polymers, is flammable as a hydrocarbon. EPDM burns quickly with high heat release and rapid flame spread, releasing a large amount of smoke and toxic gases, posing a potential threat to people's lives and property safety. Therefore, the research on flame-retardant EPDM has important practical significance for human health, safety and sustainable development.

[0003] The synergistic effect of intumescent flame retardant can enhance the flame retardant efficiency of IFR system, reduce the amount of flame retardant added, and improve the problems of poor mechanical properties and poor thermal stability of EPDM / IFR. The synergistic system mainly adds synergists such as metal oxides, nanomaterials, and compounds containing flame retardant elements to the IFR system. Among them, the combination of IFR and nanotechnology is the most widely studied. Compared with zero-dimensional nanomaterials and one-dimensional nanomaterials, two-dimensional (2D) nanomaterials have become a superior flame retardant choice due to their layered structure. They have high thermal stability and can form a physical barrier in the polymer matrix. The effectiveness of different 2D nanomaterials on the flame retardant of the substrate varies, mainly depending on the stability and composition of the nanomaterials. Uniformly dispersing a small amount of 2D nanomaterials in the polymer can effectively improve the mechanical properties of the polymer. In addition, only a small amount of 2D nanomaterials added to the polymer matrix can significantly reduce the heat release rate, total heat release and mass loss rate of the substrate, and can also play a role in suppressing smoke and reducing toxicity. At the same time, the uniformly dispersed layered structure in the polymer can not only greatly enhance the thermal stability of the polymer but also further increase the amount of residual carbon.

[0004] The flame retardant application of 2D nanomaterials mainly has defects such as easy agglomeration. At the same time, when applied to rubber substrates, it will also lead to problems such as poor interfacial compatibility and stress concentration defects caused by secondary aggregation of 2D nanomaterials. Therefore, 2D nanomaterials are often surface treated through surface functionalization modification to improve their dispersibility and compatibility in rubber substrates. Exploring the construction of hybrid materials based on 2D nanomaterials, improving the flame retardant properties of TPU substrates under different flames through synergistic effects, and giving them excellent mechanical properties is an important direction for the future development of nano-based flame retardants.

[0005] MXene is a new type of 2D layered transition metal carbide / carbonitride obtained by MAX phase treatment, where M represents early transition metal and X represents carbon or nitrogen. As a 2D nanomaterial, MXene, like other GO, ZrP and layered dihydrogen compounds, can also be used as a flame retardant synergist for traditional phosphorus-nitrogen flame retardants. However, due to the chemical inertness of transition metal carbides and nitrides, MXene lacks chemical reactivity. Therefore, surface functionalization modification of MXene is of great significance for simultaneously enhancing the mechanical properties and flame retardancy of MXene-based rubber composites. Summary of the invention

[0006] The object of the present invention is to provide a flame retardant rubber material and a preparation method thereof, so as to solve the problem of poor flame retardant performance of rubber mentioned in the background technology.

[0007] To achieve the above-mentioned purpose, the present invention provides the following technical solution: a flame retardant rubber material, characterized in that it comprises the following raw materials in parts by weight: 100 parts of EPDM rubber, 3-10 parts of ammonium phosphate grafted graphene oxide, 5-80 parts of filler, 1-5 parts of vulcanizing agent, 0.5-2 parts of vulcanization accelerator, and 5-30 parts of lubricant.

[0008] Furthermore, 1-5 parts of MXene are added.

[0009] Furthermore, the preparation steps of the ammonium phosphate grafted graphene oxide include: dissolving 10 parts of ammonium phosphate in 100 parts of water, adjusting the pH to 6.0, adding 30 parts of graphene oxide, heating to 150° C. under a protective gas atmosphere, stirring for 7 hours, and filtering and drying to obtain the result.

[0010] Furthermore, the Mxene is imidazole-modified Mxene.

[0011] Furthermore, the preparation step of the imidazole-modified Mxene includes: under a protective gas atmosphere, dispersing 1 part of Mxene in 100 parts of water, adding 3 parts of 1-vinyl imidazole, stirring at room temperature for 12 hours, filtering and drying to obtain the obtained product.

[0012] Furthermore, the imidazole-modified Mxene is grafted onto the ammonium phosphate-grafted graphene oxide.

[0013] Furthermore, the preparation steps of imidazole-modified Mxene grafted on ammonium phosphate-grafted graphene oxide include: after 2 parts of ammonium phosphate-grafted graphene oxide are evenly dispersed in 40 parts of water, 0.27 parts of potassium persulfate are added and stirred for 0.5 hours, and then 5 parts of imidazole-modified Mxene are added, the temperature is raised to 80°C and stirred for 3 hours, and the mixture is obtained after filtering and drying.

[0014] Furthermore, 1-5 parts of a C2 or higher compound containing two or more terminal thiol groups are added.

[0015] A method for preparing a flame retardant rubber material comprises the following steps: (1) after mechanically blending EPDM rubber, a lubricant and a filler, heating the mixture to 115-125° C. and kneading the mixture for 4-5 minutes, and cooling the mixture to below 80° C. after debonding to obtain a masterbatch; (2) adding the remaining materials to the masterbatch, placing the mixture in an open mixing mill, heating the mixture to 115-125° C. and kneading the mixture for 2-3 minutes, and cooling the mixture to room temperature to obtain a mixed rubber.

[0016] A sealing strip is made by extruding the above mentioned mixed rubber.

[0017] Compared with the prior art, the present invention has the following beneficial effects:

[0018] 1. Add ammonium phosphate grafted graphene oxide material to the EPDM rubber substrate, and use the rigidity of graphene macromolecules to enhance the material. Ammonium phosphate grafted on the surface of graphene oxide can reduce the agglomeration between graphenes and improve the dispersion effect of graphene. At the same time, an intumescent flame retardant system (IFR) with phosphorus as the acid source and nitrogen as the gas source is formed to achieve the flame retardant effect of the material.

[0019] 2. The thermal conductivity of MXene material is about 55W / mK, which is much lower than carbon materials such as graphene (5300W / mK) and CNT (6600W / mK). This property makes MXene a good material for fire thermal radiation shielding, and has a significant effect on further reducing the heat release of the material and increasing the residual carbon rate.

[0020] 3. MXene has the problem of easy secondary aggregation in flame-retardant polymer substrates. This project uses imidazole to modify its surface. MAX material loses aluminum ions after etching, making the surface of MXene material electronegative, while imidazole material has positive charge and will be adsorbed to the surface of MXene material and the original aluminum layer through particle interaction (electrostatic self-assembly), promoting the dispersion of MXene sheets and further expanding the interlayer spacing.

[0021] 4. 1-vinylimidazole-modified Mxene is blended with ammonium phosphate grafted graphene oxide, and potassium persulfate is used to initiate the grafting, so that 1-vinylimidazole-modified Mxene is grafted on the surface of ammonium phosphate grafted graphene oxide, which further promotes the dispersion of 1-vinylimidazole-modified Mxene compared with small molecule modified Mxene.

[0022] 5. Add a small molecule double-headed thiol compound to the mixed glue. Under the action of ultraviolet radiation or high temperature, through click chemistry reaction, one of the thiol groups can be connected to the double bond in 1-vinylimidazole, and the other thiol group can be connected to the side chain on the EPDM molecular chain, so that 1-vinylimidazole-modified Mxene or imidazole-modified Mxene grafted on ammonium phosphate grafted graphene oxide is directly grafted on the polymer chain, which not only promotes the dispersion of 1-vinylimidazole-modified Mxene or imidazole-modified Mxene grafted on ammonium phosphate grafted graphene oxide, but also enhances the mechanical properties of the material, and at the same time promotes the cross-linking between molecular chains, reduces the use of vulcanizers, reduces the VOC content of the final product, and improves the surface quality of the final product. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 It is a schematic diagram of the preparation of ammonium phosphate grafted graphene oxide in this application.

[0024] Figure 2 It is a schematic diagram of the preparation of imidazole-modified Mxene in this application.

[0025] Figure 3 It is a schematic diagram of the preparation of imidazole-modified Mxene grafted on ammonium phosphate-grafted graphene oxide in this application. Implementation

[0026] In order to make the technical means, distinguishing features, objectives and effects achieved by the present invention easy to understand, the present invention is further described below in conjunction with specific implementation methods.

[0027] Unless otherwise specified, all raw materials and reagents used in the examples of the present invention are commercially available, and the parts are by mass unless otherwise specified.

[0028] Testing method for rubber composition: Under standard laboratory environment (23°C, 55%), parameters such as tensile strength and elongation at break are implemented in accordance with GB / T 528, vertical burning grade and limiting oxygen index are implemented in accordance with GB / T 10707, smoke density grade is implemented in accordance with GB 8624, surface quality is determined by visually observing whether the surface of the film parked at room temperature for 14 days is frosted, odor grade is determined in accordance with T / CMIF 12 standard issued by China Machinery Industry Federation, VOCs evaluation is implemented in accordance with HJ / T400, and 8 parameters such as benzene, toluene, xylene, ethylbenzene, styrene, formaldehyde, acetaldehyde and acrolein are added together to determine.

[0029] The peak heat release rate (PHRR), total heat release (THR), and carbon residue rate were measured by cone calorimeter at 35 kW / m according to ISO5660-1 standard. 2 The combustion test was carried out under the heat flow of , and the sample size was 10*10*3mm 3During the test, each sample was wrapped with aluminum foil and exposed horizontally to the conical heater, with the distance between the sample surface and the bottom of the radiation cone being 23 ± 1 mm.

[0030] Preparation of MXene (Ti3C2TX): 3.1128g lithium fluoride powder was dissolved in a solution consisting of 30mL concentrated hydrochloric acid and 10mL deionized water, 2g titanium aluminum carbon powder (MAX) was slowly added, and the mixture was stirred at 38°C for 48h. After the reaction was completed, centrifugation was performed at 8000rpm, and then the centrifugal product was centrifuged and washed 3 times with 1M HCl solution and 1M LiCl solution respectively, and then repeatedly centrifuged and washed with deionized water until the pH value reached 6. The washed precipitate was evenly dispersed in 150mL deionized water, ultrasonically treated for 1h at a temperature below 20°C, and centrifuged at 3500rpm for 1h. The upper layer was the MXene nanosheet aqueous dispersion (concentration was 10mg / mL).

[0031] Preparation of 1-vinylimidazole MXene: 3 g of 1-vinylimidazole was slowly added to 100 ml of MXene nanosheet aqueous dispersion and stirred at room temperature for 12 h. After centrifugation, the mixture was washed three times with deionized water to obtain dMXene.

[0032] During the etching process, the MXene layer becomes negatively charged due to the absence of aluminum, and the remaining Li + The ions and one N on 1-vinylimidazole carry positive charges and are adsorbed onto the surface of the MXene layer through ionic electrostatic interactions.

[0033] Preparation of phosphoric acid grafted graphene oxide: At room temperature, add 10g of ammonium phosphate into a beaker, add 100ml of deionized water to dissolve and stir, add a small amount of phosphoric acid solution to adjust the pH to 6.0, then transfer it to a three-necked flask, add 30g of commercially available graphene oxide and introduce argon as a protective gas, heat to 150°C and stir for 7h, filter after cooling to room temperature, wash with anhydrous ethanol for more than three times, and obtain phosphoric acid grafted graphene oxide (P-GO) after vacuum drying.

[0034] Preparation of grafted P-GO: Take 2g of P-GO and 40ml of deionized water, add them into a three-necked flask and stir to disperse them evenly. Use argon as the protective gas, and then add the pre-mixed potassium persulfate solution (1mmol dissolved in 10ml of water) dropwise. After the addition is completed, stir for 0.5h, then add 5g of dMXene, heat to 80℃ and react for 3 hours to obtain grafted P-GO (JP-GO).

[0035] Molding process of comparative example and embodiment:

[0036] Basic formula: 100 parts of EPDM rubber, 3-10 parts of ammonium phosphate grafted graphene oxide, 5-80 parts of filler, 1-5 parts of vulcanizing agent, 0.5-2 parts of vulcanization accelerator, and 5-30 parts of lubricant.

[0037] (1) After mechanically blending EPDM rubber, lubricant and filler, the temperature is raised to 115-125°C and mixed for 4-5 minutes. After debonding, the mixture is cooled to below 80°C to obtain a masterbatch.

[0038] (2) Add ammonium phosphate grafted graphene oxide, a vulcanizing agent, and a vulcanization accelerator to the masterbatch, put it into an open mixer, heat it to 115-125° C., mix it for 2-3 minutes, and then cool it to room temperature to obtain a mixed rubber.

[0039] Filler: includes carbon black, white carbon black, calcium powder, mica powder, clay, talcum powder and other particles that have the function of reinforcing or reducing costs. In the embodiment of the present application, carbon black is selected. If necessary, the filler can be surface-modified by a coupling agent or other methods.

[0040] Lubricant: including stearic acid, zinc stearate, etc. In the embodiment of the present application, stearic acid is selected.

[0041] Vulcanizing agent: includes sulfur vulcanizing agent and peroxide vulcanizing agent (DCP, TMCH, etc.). In the embodiment of the present application, sulfur is selected.

[0042] Vulcanization accelerator: including EG-3, TMTD, etc. In the examples of the present application, EG-3 is selected.

[0043] Forming process of thiol cross-linking embodiment:

[0044] (1) After mechanically blending EPDM rubber, lubricant and filler, the temperature is raised to 115-125°C and mixed for 4-5 minutes. After debonding, the mixture is cooled to below 80°C to obtain a masterbatch.

[0045] (2) Adding ammonium phosphate grafted graphene oxide and thiol compound to the masterbatch, putting it into an open mixer, heating it to 115-125° C. and mixing it for 2-3 minutes, and then cooling it to room temperature to obtain a mixed rubber.

[0046] Thiol compound: refers to a C2 or higher compound containing two or more terminal thiol groups, especially pentaerythritol tetrathioglycolate, 4',4-dimercaptodiphenyl sulfide, 2,5-dimercaptothiadiazole, trithiocyanic acid or their homologues and derivatives, and any combination of the above compounds. In the embodiment of the present application, pentaerythritol tetrathioglycolate is selected. In the intumescent flame retardant, it can also serve as a carbon source component.

[0047] In the molding process of the mercapto cross-linking special embodiment, the vulcanizing agent and the vulcanization accelerator can be added in a small amount according to actual conditions.

[0048] A sealing strip is obtained by extruding and vulcanizing the mixed rubber of any of the comparative examples, embodiments or special embodiments described above, and can include an inner frame (including a metal frame and a plastic frame, etc.) for co-extrusion during extrusion.

[0049] The vulcanization process includes hot air vulcanization, microwave vulcanization, ultraviolet radiation cross-linking vulcanization and the like, and may also be a combination of several arrangements of these vulcanization methods.

[0050] Comparative Example 1: 100 parts of EPDM rubber, 40 parts of carbon black, 3 parts of sulfur, 1 part of EG-3 vulcanization accelerator, and 5 parts of stearic acid.

[0051] Comparative Example 2: 100 parts of EPDM rubber, 3 parts of graphene oxide, 40 parts of carbon black, 3 parts of sulfur, 1 part of EG-3 vulcanization accelerator, and 5 parts of stearic acid.

[0052] Comparative Example 3: 100 parts of EPDM rubber, 2 parts of Mxene, 40 parts of carbon black, 3 parts of sulfur, 1 part of EG-3 vulcanization accelerator, and 5 parts of stearic acid.

[0053] Comparative Example 4: 100 parts of EPDM rubber, 2 parts of MAX, 40 parts of carbon black, 3 parts of sulfur, 1 part of EG-3 vulcanization accelerator, and 5 parts of stearic acid.

[0054] Example 1: 100 parts of EPDM rubber, 3 parts of ammonium phosphate grafted graphene oxide, 40 parts of carbon black, 3 parts of sulfur, 1 part of EG-3 vulcanization accelerator, and 5 parts of stearic acid.

[0055] Example 2: 100 parts of EPDM rubber, 3 parts of ammonium phosphate grafted graphene oxide, 2 parts of Mxene, 40 parts of carbon black, 3 parts of sulfur, 1 part of EG-3 vulcanization accelerator, and 5 parts of stearic acid.

[0056] Example 3: 100 parts of EPDM rubber, 3 parts of ammonium phosphate grafted graphene oxide, 5 parts of Mxene, 40 parts of carbon black, 3 parts of sulfur, 1 part of EG-3 vulcanization accelerator, and 5 parts of stearic acid.

[0057] Example 4: 100 parts of EPDM rubber, 3 parts of ammonium phosphate grafted graphene oxide, 2 parts of MAX, 40 parts of carbon black, 3 parts of sulfur, 1 part of EG-3 vulcanization accelerator, and 5 parts of stearic acid.

[0058] Example 5: 100 parts of EPDM rubber, 3 parts of ammonium phosphate grafted graphene oxide, 2 parts of dMxene, 40 parts of carbon black, 3 parts of sulfur, 1 part of EG-3 vulcanization accelerator, and 5 parts of stearic acid.

[0059] Example 6: 100 parts of EPDM rubber, 3 parts of JP-GO, 40 parts of carbon black, 3 parts of sulfur, 1 part of EG-3 vulcanization accelerator, and 5 parts of stearic acid.

[0060] Example 7: 100 parts of EPDM rubber, 5 parts of JP-GO, 40 parts of carbon black, 3 parts of sulfur, 1 part of EG-3 vulcanization accelerator, and 5 parts of stearic acid.

[0061] Example 8: 100 parts of EPDM rubber, 3 parts of ammonium phosphate grafted graphene oxide, 2 parts of JP-GO, 40 parts of carbon black, 3 parts of sulfur, 1 part of EG-3 vulcanization accelerator, and 5 parts of stearic acid.

[0062] Tensile strength / MPa Elongation at break / % <![CDATA[PHRR / kW / m 2 ]]> <![CDATA[THR / MJ / m 2 ]]> Vertical combustion stage Limiting oxygen index / % Residual carbon rate / % Comparative Example 1 5.6 205 665.4 120.3 / 19.4 2.9 Comparative Example 2 4.7 136 626.7 117.2 / 20.1 3.6 Comparative Example 3 5.1 145 598.3 105.2 / 20.5 6.5 Comparative Example 4 5.0 162 610.4 107.0 / 20.0 5.7 Example 1 6.7 213 372.6 88.5 V-0 27.0 18.5 Example 2 6.4 192 355.2 87.3 V-0 27.2 20.4 Example 3 6.5 182 339.1 85.5 V-0 27.2 26.7 Example 4 5.9 132 365.1 88.2 V-1 26.2 21.0 Example 5 6.9 219 342.6 83.4 V-0 27.7 26.4 Example 6 7.7 243 195.0 75.7 V-0 31.2 43.4 Example 7 8.0 256 168.7 70.9 V-0 32.9 47.2 Example 8 7.9 247 172.5 72.1 V-0 31.7 46.5

[0063] Among them: The “ / ” in the vertical burning level means that it cannot pass the V-2 level test.

[0064] It can be seen from the above table that the flame retardant properties of ordinary EPDM rubber materials are poor, especially the residual carbon rate is only 2.9%. Although the addition of graphene oxide, Mxene and MAX can slightly improve the flame retardant properties of the material, it has obvious damage to the mechanical properties of the material. This is mainly because the lack of surface modification causes the material to agglomerate and directly deteriorates the mechanical properties of the material.

[0065] By observing the data of Example 1, it can be found that the graphene oxide modified by ammonium phosphate grafting has a significant effect on improving the mechanical properties of the material, especially the tensile strength. This is mainly because the graphene oxide itself is a rigid particle with good reinforcing effect. At the same time, it also has a significant effect on the reduction of PHRR and THR. This is because after the addition of ammonium phosphate grafted modified graphene oxide, when the rubber material is burned, an expansion flame retardant system with phosphorus as the acid source, ammonium as the gas source, and the material as the carbon source can be formed, which directly improves the flame retardant properties of the material and improves the residual carbon rate. From Examples 2-4, we can see that the addition of Mxene and MAX has a good effect on improving the residual carbon rate of the composite material, but the effect of improving the mechanical properties is not obvious, and there is even a phenomenon of deteriorating the mechanical properties of the material. We speculate that this is because during the combustion process, the fixed structure of the Ti-OP bond remains stable and promotes the formation of graphitized residual carbon. At the same time, the flaky MXene nanosheets in the residual carbon can act as a protective barrier and prevent the diffusion of heat and mass during the combustion of the substrate, thereby reducing the PHRR and THR values ​​of the material during combustion. From Example 5, it can be seen that the direct addition of dMXene has little effect on the various properties of the material. Looking at Examples 6-8, we can find that the imidazole-modified Mxene grafted on ammonium phosphate grafted graphene oxide (JP-GO) has a very obvious improvement in the various properties of the material, especially in Examples 7 and 8, it is shown that the various properties of the composite material are significantly improved with the addition of JP-GO. We speculate that this is because 1-vinyl imidazole-modified Mxene expands its interlayer spacing, and when it is grafted on ammonium phosphate grafted graphene oxide, the dispersion effect is significantly enhanced. Due to the low thermal conductivity of Mxene material, after full dispersion, the heat release of the material can be significantly reduced and the residual carbon rate can be increased. On the whole, JP-GO is an excellent flame retardant material, which has a good effect on improving the flame retardant properties of rubber materials.

[0066] The mixed rubber in the following examples was subjected to UV radiation crosslinking after sheeting, and the radiation crosslinking time was controlled to be 4 minutes and the UV power was controlled to be 8 kW.

[0067] Example 9: 100 parts of EPDM rubber, 5 parts of JP-GO, 40 parts of carbon black, 4 parts of pentaerythritol tetrathioglycolate, and 5 parts of stearic acid.

[0068] Example 10: 100 parts of EPDM rubber, 5 parts of dMxene, 40 parts of carbon black, 4 parts of pentaerythritol tetrathioglycolate, and 5 parts of stearic acid.

[0069] Example 11: 100 parts of EPDM rubber, 3 parts of JP-GO, 2 parts of dMxene, 40 parts of carbon black, 4 parts of pentaerythritol tetrathioglycolate, and 5 parts of stearic acid.

[0070] Example 12: 100 parts of EPDM rubber, 5 parts of JP-GO, 40 parts of carbon black, 4 parts of 1,2-dimercaptoethane, and 5 parts of stearic acid.

[0071] Tensile strength / MPa Elongation at break / % Odor level <![CDATA[VOCs / g·cm -3 ]]> <![CDATA[PHRR / kW / m 2 ]]> <![CDATA[THR / MJ / m 2 ]]> Vertical combustion stage Limiting oxygen index / % Residual carbon rate / % Comparative Example 1 5.6 205 4.5 0.60 665.4 120.3 / 19.4 2.9 Example 7 8.0 256 4.5 0.58 168.7 70.9 V-0 32.9 47.2 Example 9 8.1 260 2.0 0.28 157.4 65.6 V-0 33.1 55.2 Example 10 7.0 220 3.5 0.35 344.0 82.5 V-0 27.6 26.8 Embodiment 11 7.9 245 2.5 0.32 171.7 71.4 V-0 31.5 45.9 Example 12 8.0 251 2.0 0.28 167.5 68.9 V-0 32.7 46.8

[0072] From the data of the above embodiments and comparative examples, it is not difficult to find that the mechanical properties of the products made by irradiation cross-linking technology are almost the same as those of sulfur-cured products, or even slightly improved. We speculate that this is because one end of the dithiol compound is connected to the double bond on the imidazole in JP-GO or dMXene, and the other end is connected to the double bond on the side chain of the EPDM material, which can further promote the dispersion of JP-GO or dMXene, improve the mechanical properties and flame retardant properties of the material, and promote the cross-linking between the molecular chains of the polymer material, avoid the use of sulfur, and significantly reduce the odor level and VOC release of the material. From Examples 7 and 9, the material cross-linked with pentaerythritol tetrathioglycolate has a significant improvement in flame retardant properties. We speculate that this is because pentaerythritol tetrathioglycolate acts as a carbon source in the entire material system, further enriching the flame retardant system of the composite material. From Examples 9-11, the odor of 2-vinyl imidazole self-assembled by electrostatic adsorption on dMXene is heavier, while the odor of JP-GO after grafting is significantly reduced. From Examples 9 and 12, it can be seen that replacing pentaerythritol tetrathioglycolate with 1,2-dimercaptoethane material has little effect on the mechanical properties and odor of the product, but almost no improvement on the flame retardant properties of the material, which further confirms the flame retardant effect of pentaerythritol tetrathioglycolate on composite materials.

[0073] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It is obvious to those skilled in the art that the present invention is not limited to the details of the above exemplary embodiments, and the present invention can be implemented in other specific forms without departing from the spirit or basic features of the present invention. Therefore, no matter from which point of view, the embodiments should be regarded as exemplary and non-restrictive. The scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims are included in the present invention.

[0074] In addition, it should be understood that although this specification is described according to the implementation modes and drawings, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should take the specification as a whole. The technical solutions in each embodiment can also be appropriately combined to form other implementation modes that can be understood by those skilled in the art. The purpose of the present invention is to provide a flame retardant rubber material and a preparation method thereof to solve the problem of poor flame retardant performance of rubber mentioned in the background technology.

Claims

1. A flame retardant rubber material, characterized in that: The invention comprises the following raw materials in parts by weight: 100 parts of EPDM rubber, 3-10 parts of ammonium phosphate grafted graphene oxide, 5-80 parts of filler, 1-5 parts of vulcanizing agent, 0.5-2 parts of vulcanization accelerator, 5-30 parts of lubricant, and 1-5 parts of imidazole modified Mxene; The imidazole-modified Mxene is grafted onto the ammonium phosphate-grafted graphene oxide; The preparation steps of the ammonium phosphate grafted graphene oxide include: dissolving 10 parts of ammonium phosphate in 100 parts of water, adjusting the pH to 6.0, adding 30 parts of graphene oxide, heating to 150° C. under a protective gas atmosphere, stirring for 7 hours, filtering and drying to obtain the obtained product; The preparation steps of the imidazole-modified Mxene include: dispersing 1 part of Mxene in 100 parts of water under a protective gas atmosphere, adding 3 parts of 1-vinyl imidazole, stirring at room temperature for 12 hours, filtering and drying to obtain the obtained product; The preparation steps of imidazole-modified Mxene grafted on ammonium phosphate-grafted graphene oxide include: after 2 parts of ammonium phosphate-grafted graphene oxide are evenly dispersed in 40 parts of water, 0.27 parts of potassium persulfate are added and stirred for 0.5 hours, and then 5 parts of imidazole-modified Mxene are added, the temperature is raised to 80° C. and stirred for 3 hours, and the mixture is filtered and dried to obtain the obtained product.

2. The flame retardant rubber material according to claim 1, characterized in that: 1-5 parts of a C2 or higher compound containing two or more terminal thiol groups are also added.

3. The method for preparing a flame retardant rubber material according to claim 1, characterized in that: The steps include: (1) After mechanically blending EPDM rubber, lubricant and filler, the temperature is raised to 115-125°C and mixed for 4-5 minutes. After debonding, the mixture is cooled to below 80°C to obtain a masterbatch. (2) Add the remaining materials to the masterbatch, put it into an open mixer, heat it to 115-125°C and mix it for 2-3 minutes, and then cool it to room temperature to obtain a mixed rubber.

4. A sealing strip, characterized in that: The rubber compound is obtained by extruding the rubber compound obtained by the preparation method according to claim 3.

Citation Information

Patent Citations

  • Poly-mercapto compound-containing white carbon black-filled rubber composite material and preparation method thereof

    CN107022126A

  • Modified ethylene propylene terpolymer and preparation method

    CN107236199A

  • Method for immobilizing MXene by covalent bonding of ionic liquid and product thereof

    CN111785534A

  • Fire-retarding composition, process for production of the composition, fire- retarding mixture comprising the composition and treatment of fabrics with the composition

    US20210076762A1